In the Process of Being Bilingual of an Indonesian Child: The Phenomena of Code-Switching, Language Mixing and Borrowing - Lisda Nurjaleka; Rina Supriatnaningsih (UIN Salatiga, 2021)
The present study is a longitudinal study for approximately 26 months to the Indonesian child and has been through her second language acquisition in Japan. A Longitudinal study is a research design that involved repeated observation of the same variables over long periods. The acquisition process took place for about four years. After returning to Indonesia, the family wants to keep her second language and do some second language maintenance. While in her process to be bilingual, she experienced a process of code-switching and code-mixing in her daily life using their mother tongue, Indonesian, and her second language, Japanese. This research focuses on how the child maintains her second language and how the bilingual process's phenomena occur through interactions in the family environment. Several language transfers from the second language to the first language occur in their daily life using Indonesian. This study uses an ethnographic research approach. Conducting ethnographic research requires a long-term process by making detailed notes about the group's behavior and beliefs from time to time. Observation and interviews are the procedures used in data collection in the field. The transfer language process is used through the code-mixing, code-switching, and preservation process of the second language after returning home. The results saw that the child both uses language systems in each language and sometimes mixed in between languages, as she has her languages.Keywords: code-switching; language mixing; Japanese as a second language; bilingual process